Disentangling molecular mechanisms regulating sensitization of interferon alpha signal transduction. Issue 7 (21st July 2020) - Kok, Frédérique; Rosenblatt, Marcus; Teusel, Melissa; Nizharadze, Tamar; Gonçalves Magalhães, Vladimir; Dächert, Christopher; Maiwald, Tim; Vlasov, Artyom; Wäsch, Marvin; Tyufekchieva, Silvana; Hoffmann, Katrin; Damm, Georg; et al.
Abstract: Tightly interlinked feedback regulators control the dynamics of intracellular responses elicited by the activation of signal transduction pathways. Interferon alpha (IFNα) orchestrates antiviral responses in hepatocytes, yet mechanisms that define pathway sensitization in response to prestimulation with different IFNα doses remained unresolved. We establish, based on quantitative measurements obtained for the hepatoma cell line Huh7.5, an ordinary differential equation model for IFNα signal transduction that comprises the feedback regulators STAT1, STAT2, IRF9, USP18, SOCS1, SOCS3, and IRF2. The model‐based analysis shows that, mediated by the signaling proteins STAT2 and IRF9, prestimulation with a low IFNα dose hypersensitizes the pathway. In contrast, prestimulation with a high dose of IFNα leads to a dose‐dependent desensitization, mediated by the negative regulators USP18 and SOCS1 that act at the receptor. The analysis of basal protein abundance in primary human hepatocytes reveals high heterogeneity in patient‐specific amounts of STAT1, STAT2, IRF9, and USP18. The mathematical modeling approach shows that the basal amount of USP18 determines patient‐specific pathway desensitization, while the abundance of STAT2 predicts the patient‐specific IFNα signal response. Synopsis: Mathematical modeling based on quantitative data reveals the molecular mechanisms that cause hypersensitization of interferon alpha (IFNα) signaling by pre‐exposure with a low dose of IFNα and desensitization with a high dose of IFNα. IFNα induces the formation of the pSTAT1:pSTAT1, pSTAT1:pSTAT2 and pSTAT1:pSTAT2:IRF9 (ISGF3) transcription factor complexes in a temporal and dose‐dependent order. IRF9 is induced with low doses of IFNα and causes pathway hypersensitization by favoring the ISGF3 transcription factor complex. Both USP18 and SOCS1 foster desensitization of the IFNα signal transduction pathway. The patient‐specific abundance of USP18 defines the desensitization threshold, while the abundance of STAT2 is a predictor for the antiviral response of an individual patient. Abstract : Mathematical modeling based on quantitative data reveals the molecular mechanisms that cause hypersensitization of interferon alpha (IFNα) signaling by pre‐exposure with a low dose of IFNα and desensitization with a high dose of IFNα.